DNA-cellulose: an economical, fully recyclable and highly effective chiral biomaterial for asymmetric catalysis1. Issue 28 (11th April 2015) - Benedetti, Erica; Duchemin, Nicolas; Bethge, Lucas; Vonhoff, Stefan; Klussmann, Sven; Vasseur, Jean-Jacques; Cossy, Janine; Smietana, Michael; Arseniyadis, Stellios
<x xml:space="preserve">Abstract</x> We report here the first generation of a DNA-based catalyst bound to a cellulose matrix. The chiral biomaterial is commercially available, trivial to use, highly selective and fully recyclable.